2016
DOI: 10.1016/j.brat.2016.09.011
|View full text |Cite
|
Sign up to set email alerts
|

Reducing risk for anxiety and depression in adolescents: Effects of a single-session intervention teaching that personality can change

Abstract: Efforts to reduce youth mental health problems have advanced greatly but have not lowered overall rates of youth mental illness. Thus, a need exists for disseminable, mechanism-targeted approaches to reducing risk of youth psychopathology. Accordingly, we conducted a randomized-controlled trial testing whether a single-session intervention teaching growth personality mindsets (the belief that personality is malleable) reduced known risk factors for anxiety and depression in adolescents experiencing or at risk … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
134
2
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 127 publications
(145 citation statements)
references
References 101 publications
7
134
2
2
Order By: Relevance
“…In one study (Yeager, Lee, et al, 2016, Study 1), implicit theories of personality-theories about whether social and moral characteristics are fixed and cannot be developed-were related to high school students' threat appraisals (i.e., ratio of perceived demand to perceived resources) and HPA-axis activation (i.e., cortisol levels) following a controlled social stressor (the Trier Social Stress Test; Kirschbaum, Pirke, & Hellhammer, 1993). These findings were replicated in a sample of adolescents with elevated internalizing symptoms (Schleider & Weisz, 2016), and in a daily diary and cortisol sampling study (Yeager, Lee, et al, 2016, Study 2). However, to date, no empirical research has examined associations between implicit theories of intelligence, naturalistic academic stressors in high school, and HPA-axis activation.…”
Section: Implicit Theories Of Intelligencementioning
confidence: 80%
“…In one study (Yeager, Lee, et al, 2016, Study 1), implicit theories of personality-theories about whether social and moral characteristics are fixed and cannot be developed-were related to high school students' threat appraisals (i.e., ratio of perceived demand to perceived resources) and HPA-axis activation (i.e., cortisol levels) following a controlled social stressor (the Trier Social Stress Test; Kirschbaum, Pirke, & Hellhammer, 1993). These findings were replicated in a sample of adolescents with elevated internalizing symptoms (Schleider & Weisz, 2016), and in a daily diary and cortisol sampling study (Yeager, Lee, et al, 2016, Study 2). However, to date, no empirical research has examined associations between implicit theories of intelligence, naturalistic academic stressors in high school, and HPA-axis activation.…”
Section: Implicit Theories Of Intelligencementioning
confidence: 80%
“…In another study, entering ninth‐graders who took part in the incremental theory intervention showed 40% fewer depressive symptoms 8–9 months after the intervention, and the effect was more prominent for those who started the year ascribing to an entity theory of personality . In a replication study, this effect on internalizing symptoms did not generalize to a group of entering college students a month later , but in a different replication study, the effect on physiological reactivity that precedes internalizing symptoms generalized to clinically referred adolescents . These initial results are encouraging enough to continue replications, but the intervention is not ready to be implemented at full scale.…”
Section: Changing Implicit Theories Through Psychological Interventionmentioning
confidence: 96%
“…Physiologically, threat ‐type appraisals lead to cardiovascular and hormonal responses that prepare the body for damage and defeat: constricted blood vessels and secretion of cortisol (activation of the HPA axis; ). Ascribing to an incremental theory, which promotes more challenge‐type appraisals, reduces adolescents’ threat‐type physiological responses when they are evaluated negatively by a peer (; see also for a replication).…”
Section: Implicit Theories: High School Social Life From Two Perspectmentioning
confidence: 99%
“…In two trials of growth mindset SSIs, significant effects on proposed intervention mechanisms were observed. In one trial, adolescents receiving a growth mindset SSI (versus a control SSI) reported greater increases in growth mindset, primary perceived control, and perceived secondary perceived control immediately post-intervention (Schleider & Weisz, 2016). Effects on primary perceived control, but not secondary control, persisted at a 9-month follow-up (Schleider & Weisz, 2018).…”
Section: Self-administered Ssis Since 2016mentioning
confidence: 99%
“…following SSIs, where symptom changes emerge months after an SSI but changes in other outcomes are detectable immediately (Schleider & Weisz, 2016;Schleider & Weisz, 2018). Some have suggested that brief interventions may exert 'delayed' impacts on outcomes of interest by triggering recursive learning processes.…”
Section: Future Directions In Evaluating Ssismentioning
confidence: 99%